Impact of organizational commitment and work motivation on employee performance airnav Juanda International Airport - Munda, Erwin; Rahayu, Sri; Hardjanti, Wulandari; Sundjoto; Supardam, Dhian (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to analyze the effect of organizational commitment and work motivation on employee performance at AIRNAV Indonesia Surabaya branch Juanda International Airport. The research sample involved 20 employees by using the entire population as respondents. Data collection techniques were conducted through questionnaires, interviews, and documentation, while data analysis used multiple linear regression. The results showed that organizational commitment and work motivation partially and jointly have a positive and significant effect on employee performance. The findings highlight the importance of organizational efforts in increasing the level of commitment and motivation of employees to advance their performance. The implication of this study can contribute to the organization's management in developing more effective strategies to improve employee welfare and productivity in AIRNAV Indonesia's aviation work environment.